A New Strategy for Enhancing Postharvest Quality of Sweet Cherry: High-Voltage Electrostatic Field Improves the Physicochemical Properties and Fungal Community - Yanlong Liu; Lulu Zhang; Tan Hu; Qiongyin Liu; Shuya Zhou; Yi Zhao; Abdul-Nabi Jatt; Caili Zhang; Hansheng Gong (Foods)
Sweet cherry has a short shelf life due to the occurrence of senescence and fungal infection after harvest. This study aimed to study the effects of high-voltage electrostatic field (HVEF) on the physicochemical properties and fungal composition of sweet cherry during cold storage. The experiments were conducted at 4 °C for 28 days and the quality indicators were determined every 7 days during the period of storage. The fungal composition on sweet cherry was determined using high-throughput sequencing. The results showed that HVEF could better maintain the total soluble solids and inhibit the respiration of cherries. The decay incidence in sweet cherries was decreased by HVEF during cold storage. High-throughput sequencing revealed that HVEF could alter the fungal community and increase the fungal diversity on sweet cherries. Compared with the control group, HVEF decreased the abundance of Alternaria and Cladosporium on sweet cherries, while Aureobasidium, as a nonpathogenic fungus, increased and became the dominant strain at the end of the storage period. In summary, HVEF can improve the physicochemical properties of sweet cherry by inhibiting respiration and can reduce decay incidence by inhibiting specific pathogenic fungi. HVEF is expected to become an efficient and promising technology for the preservation of fruit.